Endoscopic ultrasound with tissue acquisition of lymph nodes in patients with potentially resectable intrahepatic cholangiocarcinoma - de Jong, David M.; van de Vondervoort, Sanne; Dwarkasing, Roy S.; Thomeer, Maarten G.J.; Doukas, Michael; Voermans, Rogier P.; Verdonk, Robert C.; Polak, Wojciech G.; de Jonge, Jeroen; Bruno, Marco J.; Van Driel, Lydi M.J.W.; Groot Koerkamp, Bas (Endoscopy International Open, 2024)
Background and study aims Lymph node (LN) involvement is a poor prognostic factor for patients with intrahepatic cholangiocarcinoma (iCCA). The aim of this study was to evaluate the yield and impact on clinical decision making of endoscopic ultrasound with tissue acquisition (EUS-TA) of LNs in patients with potentially resectable iCCA.Patients and methods In this multicenter cohort study, patients with potentially resectable iCCA and preoperative EUS between 2010 and 2020 were retrospectively included. The impact of EUS-TA was defined as the percentage of patients who did not undergo surgical exploration due to pathologically confirmed positive LNs found with EUS-TA.Results A total of 56 patients underwent EUS, with 91% of patients to target suspicious LNs on imaging. EUS-TA of LNs confirmed malignancy in 21 LNs among 19 patients (34%). In 17 patients (30%), surgical exploration was withheld due to nodal involvement. Finally, 24 patients (43%) underwent surgical exploration among whom positive regional LNs were identified in six patients (25%).Conclusions In patients with potentially resectable iCCA and suspicious LNs on cross-sectional imaging, EUS-TA confirmed LN involvement in 30% of patients. Surgical exploration was withheld mostly because of extraregional LN involvement and regional LN involvement in patients with high surgical risk.
Keywords: Endoscopic ultrasonography; Biliary tract; Tissue diagnosis; Fine-needle aspiration/biopsy; GI surgery